2008
DOI: 10.1074/jbc.m803516200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Molecular Interactions between Eosinophil Cationic Protein and Heparin

Abstract: Eosinophil cationic protein (ECP) is currently used as a biomarker for airway inflammation. It is a heparin-binding ribonuclease released by activated eosinophils. Its cytotoxicity toward cancer cell lines is blocked by heparin. The objective of this study was to locate the heparin binding site of ECP by sitedirected mutagenesis and construction of a synthetic peptide derived from this region. Synthetic heparin with >5 monosaccharide units showed strong inhibition of ECP binding to the cell surface. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…This interaction is neither observed in crystal structures of ECP with a bound substrate mimics (1H1H) 24 nor without (1QMT nor 1DYT) nor in the solution structures of the ECP homologs human RNase 1 (2k11) 35 nor bovine pancreatic RNase A (2AAS). 36 Interestingly, the Tyr33 side chain, which is located in the region involved in ECP binding to heparin 25 has been recently reported to be nitrated during eosinophil maturation. 37 We propose that the nitration of Tyr33, which would endow its aromatic ring with a negative charge, could be expected to enhance its interaction with the positively charged ammonium group of Lys38.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction is neither observed in crystal structures of ECP with a bound substrate mimics (1H1H) 24 nor without (1QMT nor 1DYT) nor in the solution structures of the ECP homologs human RNase 1 (2k11) 35 nor bovine pancreatic RNase A (2AAS). 36 Interestingly, the Tyr33 side chain, which is located in the region involved in ECP binding to heparin 25 has been recently reported to be nitrated during eosinophil maturation. 37 We propose that the nitration of Tyr33, which would endow its aromatic ring with a negative charge, could be expected to enhance its interaction with the positively charged ammonium group of Lys38.…”
Section: Discussionmentioning
confidence: 99%
“…ECP shows a high binding affi nity to heparin and inhibits the enzyme RNase activity (Torrent et al , 2011a ). Critical residues involved in the interaction were identifi ed by molecular docking (Torrent et al , 2011a ) and NMR spectroscopy (Garc í a-Mayoral et al, 2010 ) and corroborated by mutagenesis studies (Fan et al , 2008 ). In particular, the 33 -38 stretch is involved in ECP binding to GAGs ( Figure 2) (Fan et al , 2008 ;Torrent et al , 2011a ).…”
Section: Dissecting Ecp Antimicrobial Mechanism Of Actionmentioning
confidence: 96%
“…Critical residues involved in the interaction were identifi ed by molecular docking (Torrent et al , 2011a ) and NMR spectroscopy (Garc í a-Mayoral et al, 2010 ) and corroborated by mutagenesis studies (Fan et al , 2008 ). In particular, the 33 -38 stretch is involved in ECP binding to GAGs ( Figure 2) (Fan et al , 2008 ;Torrent et al , 2011a ). The protein interaction with heparan sulphate at the matrix of epithelial cells would facilitate the protein endocytosis (Fan et al , 2007 ).…”
Section: Dissecting Ecp Antimicrobial Mechanism Of Actionmentioning
confidence: 99%
“…Residues Arg 1, Arg 7 and Arg 34 were predicted by molecular docking to provide the main driving force for heparin probe binding (Torrent et al, 2011a), and NMR spectroscopy data confirmed interactions between the a1 and b1 N-terminus secondary structure elements and the IdoA(2S)-GlcNS(6S) disaccharide (García-Mayoral et al, 2010). Residues 33-36 in L3 loop were also identified to be involved in heparin binding by site-directed mutagenesis (Fan et al, 2008), and a recent study on ECP antiparasitic activity identified Arg 34 as the key basic surface exposed residue (Singh and Batra, 2011). Interestingly, additional contribution of Arg 1 and Arg 7 is observed by NMR for an extended heparin probe (García-Mayoral et al, 2010, unpublished results).…”
Section: Ecp Unique Distribution Of Basic Clustersmentioning
confidence: 79%